Pelatihan Pengolahan Data Time Series dan Panel untuk Analisis Regresi dengan Menggunakan EViews-10 - Azhari, Azhari; Yusuf, M.; Jamaluddin, Jamaluddin; Afriana, Afriana; Yanna, Sri (Aceh Journal of Community Engagement (AJCE), 2023)
Community service activities are one of the lecturers' tri dharma. Service activities were carried out by 5 (five) service members in the form of training in econometric research data processing using time series data and panel data. The software used is EViews version 10. EViews is a Windows-based computer program that is widely used for statistical analysis and is a computational tool for time series econometrics. The training, which was attended by 15 young lecturers, supervisors and final year students, was held in the Aceh Care Cooperative community for 2 days, namely 12-13 August 2023 with the aim of, among other things, being able to understand the steps of analytical methods and the basics of econometric research. . , with model analysis through regression, participants are able to process time series and panel data with EViews and understand how to detect the results.